Deslocamentos Identitários de Professores no Discurso sobre sua Prática de Avaliação no Processo de Educação Continuada - Fernanda de Fatima Serakides Hon (2009)
In this study we investigate the representations of teachers of English as a foreign language who work for public schools in the city of Belo Horizonte/MG and its surroundings about language, foreign language and its assessment process. Our central point is mainly based on the discourse (re)produced by those in-service teachers about assessment within a continuing education program. This study adopts some of the most important Discourse Analysis and Psychoanalysis concepts to analyze its data related to the assessment process of the foreign language so that this work has the typical interdisciplinary characteristic of the Applied Linguistics area. Through a discursive perspective webelieve that peoples identity and their discourse are socially, historically and ideologically built and they are forever incomplete and constituted in and by language. Because of that in this research we present the concept of a historically built assessment in the fields of Education as well as Applied Linguistics. Our corpus is based on the discourse of participant teachers of a continuing education program. Through audio-recorded interviews with these teachers at the beginning and at the end of thiscourse and also through class observation notes we had access to the participant teachers discourse and their representations which produce effects in their learning of the foreign language and their professional practice. We also tried to observe the (possible) identity movements in the teachers discourse and their contradictions concerning the assessment process along their participation in the continuing education program. The analysis developed here is based on the concepts of interpretation, discursive resonances, which are the repetition of lexical choices that contribute to a predominant meaning, and contradiction. Through our interpretation gestures of the heterogeneity, conflicts andcontradictions present in the participant teachers discourse we tried to observe their representations about language, foreign language and its assessment process. We could notice that these teachers areconstituted by several representations and that these representations produce effects in their teaching practice even unconsciously. In this way, we discuss the effects of the scientific discourse (or university discourse) produced by the continuing education program on the discourse of theseparticipant teachers because many times they are resistant to external movements, and only repeat the new concepts but do not really use them in their pedagogical practice.